The Influence of Brand Image and Brand Trust on Brand Loyalty in Alya Aya Wet Food Products in Banyuates Sampang - Ridoi*, Muhammad Fariz; Pambudi, Bambang Setiyo (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2023)
This study aims to determine how much influence brand image and brand trust have on product industry brand loyalty in MSMEs in Banyuates Sampang. This research method uses a quantitative approach. The object of this study is the product industry. The subjects of this study are MSME business actors in Banyuates Sampang. Home industry is one form of business activity that has the ability to develop the economy. This ability can bring opportunities to create attractiveness and competitiveness. Brand loyalty has a meaning as the power to be different or have certain advantages over others. The excellence of a company grows from the value or benefits that the company can create for its buyers. Brand image has a concept related to the perception of a brand that is established as an association that exists in the memory of consumers. A strong brand image can influence consumers to meet their needs. Along with the rapid development of digital technology, many marketing activities are carried out online. Brand trust has become an influential component of business activities in improving business performance. This is because consumers today spend more time through digital platforms for various purposes ranging from brand information to final product purchases. Therefore, to find out how the influence of brand image and brand trust on brand loyalty, the author is interested in conducting research with the title "". The influence of brand image and brand trust on brand loyalty in Alya Aya Banyuates Sampang wet food products.